2017
DOI: 10.1016/j.surfcoat.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Thermal durability and fracture behavior of layered Yb-Gd-Y-based thermal barrier coatings in thermal cyclic exposure

Abstract: The effects of structural design on the thermal durability of Yb-Gd-Y-based thermal barrier coatings (TBCs) were investigated through thermal cyclic exposure tests, such as furnace cyclic thermal fatigue (FCTF) and jet engine thermal shock (JETS) tests. The effects of composition in the bond coat and feedstock purity for the buffer layer on its lifetime performance were also examined. To overcome the drawbacks of Yb-Gd-Y material with poor thermal durability due to poor mechanical properties and low coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…where and are the CTEs of the top coat and the bond coat (CTE is 9-10 × 10 -6 K −1 for bulk YGYZ, 10.5-11.5 × 10 -6 K −1 for YSZ, and 15.0 × 10 -6 K −1 for metallic bond coat at 1000 °C [30][31][32]), respectively, the is the mean temperature in the top coat, and…”
Section: Effect Of Buffer Layer Purity On Tbc Durabilitymentioning
confidence: 99%
“…where and are the CTEs of the top coat and the bond coat (CTE is 9-10 × 10 -6 K −1 for bulk YGYZ, 10.5-11.5 × 10 -6 K −1 for YSZ, and 15.0 × 10 -6 K −1 for metallic bond coat at 1000 °C [30][31][32]), respectively, the is the mean temperature in the top coat, and…”
Section: Effect Of Buffer Layer Purity On Tbc Durabilitymentioning
confidence: 99%
“…The partially yttrium-oxide-stabilized zirconia powder and coating have been previously prepared. 9.5Y 2 O 3 -5.6Yb 2 O 3 -5.2Gd 2 O 3 doped in ZrO 2 (YYG) was thought to have promising applications as a ceramic thermal barrier coating material in high-temperature environments due to its low thermal conductivity and high-temperature phase stability [24,25]. Its disadvantage is its poor thermal shock resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Bahamirian et al [22] investigated the ZGYbY compound and reported that Yb-Gd-Y dopants in ZrO 2 promoted the formation of highly stable nontransformable (t´) zirconia phase. Also, Jung et al [29] examined the ZGYbY-based TBCs and showed that this compound possesses a considerable high-temperature sintering resistance introducing it as a coating with relatively high thermal barrier characteristics.…”
Section: Introductionmentioning
confidence: 99%